Economy vs History - What Does Actually Determine the Distribution of Shops' Locations in Cities? - Helge Sanner (European Regional Science Association (ERSA), 2005)
This study examines in which cases economic forces or historical singularities prevail in the determination of the spatial distribution of retail shops. We develop a relatively general model of location choice in discrete space. The main force towards an agglomerated structure is the reduction of transaction costs for consumers if retailers are located closely, whilst competition and transport costs work towards a disperse structure. We assess the importance of the initial conditions by simulating the resulting distribution of shops for identical economic parameters but varying initial settings. If the equilibrium distributions are similar we conclude that economic forces have prevailed, while dissimilarity indicates that 'history' is more important. The (dis)similarity of distributions of shops is calculated by means of a metric measure.
Keywords: 330